Pemanfaatan Simulasi PhET Berbantuan LKPD sebagai Media Pembelajaran Interaktif pada Materi Hukum Hooke - Febby Apriani; Almira Erika Putri; Rindi Sartika Dwi Oktari; Gunawan Gunawan (Indonesian Publication Center, 2026)
This study aims to examine the use of PhET simulations assisted by students’ worksheets as an interactive learning medium for Hooke's Law. This study used a descriptive observation method with 32 students in grade XI Mathematics and Natural Sciences at SMAN 5 Mataram. Data collection techniques included observing student activities during the learning process and documenting the worksheet results. The results of the observations indicated that the use of PhET simulations assisted by worksheets increased student engagement and activeness during the learning process. Students appeared more enthusiastic in conducting virtual experiments, discussing, and analyzing the relationship between force and the increase in spring length. Furthermore, the virtual simulations helped students visualize the abstract concept of Hooke's Law, making the material easier to understand compared to conventional learning. The use of worksheets also helped students make observations and draw conclusions more systematically. Based on the research findings, it can be concluded that the use of PhET simulations assisted by worksheets can be an effective alternative learning medium for increasing student engagement and understanding of physics concepts in Hooke's Law.